Teaching through performance: taking second-year band students to concert performance assessment (CPA) - Jerrell, Brittany Nicole Belcher (Kansas State University, 2024)
The purpose of this project was to reinforce the transition from beginning band pedagogy to advanced ensemble rehearsal techniques and performance skills with second-year band students by separating them from third year-band students and implementing conceptual teaching methods to the process of preparation and performance for Concert Performance Assessment (CPA.) Over several years of observation in my middle school band program, I hypothesized that second-year band students would develop a greater depth of individual musical understanding as well as have a more relevant and impactful experience in the Concert Performance Assessment process if they were formally adjudicated at their current ability level, rather than combined with third-year students. By separating the second and third-year students, the CPA preparation and performance process proved to be better pedagogically aligned to the second-year students’ abilities and level of understanding, which increased students’ interest, investment, and enjoyment. This project incorporated the use of rehearsal techniques, approach to score-study and literature selection, research on conceptual teaching, discussions on the relevance of large instrumental ensembles in music education, and literature on teaching through performance which were acquired through my master’s studies. As a result, my second-year students not only exhibited substantial growth in their advanced ensemble rehearsal techniques and performance skills, but they also displayed an enthusiasm for, and understanding of, the application of growth mindset which culminated in an overwhelmingly positive student experience and performance outcome. Over the course of my master’s degree, I expanded my knowledge and depth of understanding of teaching techniques and methodologies in instrumental music education, specifically band. As a middle school band director there is a responsibility to be fluid and competent in both beginning band pedagogy and traditional band pedagogy or rehearsal techniques. However, prior to this degree I found it difficult to pinpoint or articulate how to transition students and my teaching from one to the other, which resulted in inefficiency and gaps in students’ knowledge and experiences. Through my studies in this program, I redefined my approach to these responsibilities in two significant ways. The first is in the application of the ideologies and methods outlined by the Teaching through performance (1997) series in combination with the application of intentional score-study and literature analysis. By redefining the purpose of the literature that both myself and my students study, the depth at which it is studied, and the techniques used in rehearsal, I have strengthened the quality of my instructional content and created an intentional infrastructure to sequence future curriculum. The second significant impact is in the evolution of my teaching philosophy through the discourse on the relevance of large instrumental music ensembles in modern music education in addition to a deeper understanding of the intertwined history of music education and wind band. The perspective presented through the master’s coursework has strengthened my belief that large instrumental ensembles and their musical experiences offer the opportunity for comprehensive music education that can be accessible to all students when led by discerning and consciously reflective and introspective music educators.
Keywords: Band; Teaching through performance; Middle school band; Concept teaching; Performance assessment; 7th grade band